Question
upstudy study bank question image url

Evaluate the function \( f(x)=x^{2}+9 x+1 \) at the given values of the independent variable and simplify. \( \begin{array}{lll}\text { a. } f(-8) & \text { b. } f(x+5) & \text { c. } f(-x)\end{array} \)

Ask by Guzman Reeves. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

a. \( f(-8) = -7 \) b. \( f(x+5) = x^{2} + 19x + 71 \) c. \( f(-x) = x^{2} - 9x + 1 \)

Solution

Let's evaluate the function \( f(x) = x^{2} + 9x + 1 \) for the given inputs. ### a. \( f(-8) \) To find \( f(-8) \), substitute \( x = -8 \) into the function: \[ f(-8) = (-8)^2 + 9(-8) + 1 \] Calculate each term: \[ (-8)^2 = 64 \] \[ 9(-8) = -72 \] \[ 1 = 1 \] Now, add them together: \[ f(-8) = 64 - 72 + 1 = (-8) + 1 = -7 \] **Answer:** \( f(-8) = -7 \) --- ### b. \( f(x+5) \) To find \( f(x+5) \), substitute \( x+5 \) into the function wherever there is an \( x \): \[ f(x+5) = (x + 5)^2 + 9(x + 5) + 1 \] Expand and simplify each term: 1. Expand \( (x + 5)^2 \): \[ (x + 5)^2 = x^2 + 10x + 25 \] 2. Expand \( 9(x + 5) \): \[ 9(x + 5) = 9x + 45 \] 3. Add all the terms together: \[ f(x+5) = x^2 + 10x + 25 + 9x + 45 + 1 \] Combine like terms: \[ x^2 + (10x + 9x) + (25 + 45 + 1) = x^2 + 19x + 71 \] **Answer:** \( f(x+5) = x^{2} + 19x + 71 \) --- ### c. \( f(-x) \) To find \( f(-x) \), substitute \( -x \) into the function wherever there is an \( x \): \[ f(-x) = (-x)^2 + 9(-x) + 1 \] Calculate each term: \[ (-x)^2 = x^2 \] \[ 9(-x) = -9x \] \[ 1 = 1 \] Now, combine them: \[ f(-x) = x^2 - 9x + 1 \] **Answer:** \( f(-x) = x^{2} - 9x + 1 \)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To evaluate the function \( f(x) = x^{2} + 9x + 1 \) at the given values, let's compute each part step by step. **a.** To find \( f(-8) \): \[ f(-8) = (-8)^{2} + 9(-8) + 1 \] Calculating \( f(-8) \): \[ f(-8) = 64 - 72 + 1 = -7 \] So, \( f(-8) = -7 \). --- **b.** To evaluate \( f(x + 5) \): \[ f(x + 5) = (x + 5)^{2} + 9(x + 5) + 1 \] Expanding \( f(x + 5) \): \[ = (x^{2} + 10x + 25) + (9x + 45) + 1 \] \[ = x^{2} + 10x + 25 + 9x + 45 + 1 \] \[ = x^{2} + 19x + 71 \] So, \( f(x + 5) = x^{2} + 19x + 71 \). --- **c.** Now, let's compute \( f(-x) \): \[ f(-x) = (-x)^{2} + 9(-x) + 1 \] Calculating \( f(-x) \): \[ = x^{2} - 9x + 1 \] So, \( f(-x) = x^{2} - 9x + 1 \). --- In summary: - \( f(-8) = -7 \) - \( f(x + 5) = x^{2} + 19x + 71 \) - \( f(-x) = x^{2} - 9x + 1 \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy